Meta-analysis: Validity of Atlas Development as a Supplement to High School Biology Teaching Materials - Mutiara Ratu Salsabila; Relsas Yogica; Helendra Helendra; Ria Anggriyani (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the validity and effectiveness of the Learning Atlas as a supplementary teaching material in Biology education. Supplementary teaching materials, such as the Learning Atlas, provide an alternative medium for enhancing students' comprehension of biological concepts by presenting information visually, without requiring direct observation of the phenomena. The Atlas is designed to help students engage with and absorb complex material more effectively, supporting traditional classroom learning. Methodology: The research employs a meta-analysis approach by systematically reviewing source articles obtained via Google Scholar. The sample includes 12 journals and theses related to the development and validation of the Learning Atlas and similar booklets as educational tools in Biology. Data from these sources were synthesized to assess the validity and impact of the Atlas. Main Findings: The validity of the Learning Atlas as a teaching supplement was found to be 95.55%, categorizing it as “very valid.” Additionally, the reviewed studies highlight that the Atlas effectively enhances students’ conceptual understanding and engagement in Biology learning, making abstract ideas more tangible and accessible. Novelty/Originality of this study: This research provides new insights into the use of the Learning Atlas as a practical and highly valid supplementary tool for Biology education. Unlike conventional resources, the Atlas integrates visual and textual content to support independent and classroom learning, offering educators a reliable and innovative way to enhance students’ mastery of biological concepts. It also underscores the potential for the Atlas to improve learning outcomes in diverse educational settings.